Perjuangan Mengukuhkan Identitas Nasional: Aneksasi Rusia di Krimea dalam Perspektif Konstruktivisme - Lintank Wahyu Sudibyo; Tri Cahyo Utomo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Annexation of Crimea by the Russian Federation through the Crimean declaration of independence from Ukraine and the Crimean referendum, as well as the treaty signed by the Russian government in March 2014 have made Crimea as de facto join with 21 other republics within Russian territory. However, most of the international community considers that the Crimean referendum is illegal and violates the international law. Because Russia is considered violating Ukraine territorial integrity through the presence of Russian military which is considered to affect the legality of the referendum. This study aims to analyze Russian identity influences Russian foreign policy in the annexation of Crimea. The identity in this case is the Russian national identity which is ‘personal identity’ in constructivism perspective constructed from Russian domestic concepts or ideas rooted in Russian ethnic, demographic, historical, and spiritual backgrounds that are closely related to Crimea, as well as Russian national identity is on the rise under Vladimir Putin. It will also explain the history, status, and progress of the annexation of Crimea, as well as international sanctions against Russia and the Crimea until 2017.